The census of interstellar complex organic molecules in the Class I hot corino of SVS13-A. Issue 2 (12th November 2018) - Bianchi, E; Codella, C; Ceccarelli, C; Vazart, F; Bachiller, R; Balucani, N; Bouvier, M; De Simone, M; Enrique-Romero, J; Kahane, C; Lefloch, B; López-Sepulcre, A; et al.
ABSTRACT: We present the first census of the interstellar Complex Organic Molecules (iCOMs) in the low-mass Class I protostar SVS13-A, obtained by analysing data from the IRAM-30 m Large Project ASAI (Astrochemical Surveys At IRAM). They consist of a high-sensitivity unbiased spectral survey at the 1mm, 2mm, and 3mm IRAM bands. We detected five iCOMs: acetaldehyde (CH3 CHO), methyl formate (HCOOCH3 ), dimethyl ether (CH3 OCH3 ), ethanol (CH3 CH2 OH), and formamide (NH2 CHO). In addition, we searched for other iCOMs and ketene (H2 CCO), formic acid (HCOOH) and methoxy (CH3 O), whose only ketene was detected. The numerous detected lines, from 5 to 37 depending on the species, cover a large upper level energy range, between 15 and 254 K. This allowed us to carry out a rotational diagram analysis and derive rotational temperatures between 35 and 110 K, and column densities between 3 × 10 15 and 1 × 10 17 cm −2 on the 0.3 arcsec size previously determined by interferometric observations of glycolaldehyde. These new observations clearly demonstrate the presence of a rich chemistry in the hot corino towards SVS13-A. The measured iCOMs abundances were compared to other Class 0 and I hot corinos, as well as comets, previously published in the literature. We find evidence that (i) SVS13-A is as chemically rich as younger Class 0 protostars, and (ii) the iCOMs relative abundances do not substantially evolve during the protostellar phase.